About Professional Values of Accountants Employment Behavior - Natal’ya A. Mislavskaya (Учёт. Анализ. Аудит)
Topic. The issues of establishing professional values for accountants and auditors in Russia are becoming increasingly important. It is justified by the need to increase the responsibility of accountants for providing reliable information on the financial position and performance of economic entities both to external and internal users of financial statements. The variety of accounting methods to reflect economic events and different interests of different users of accounting (financial) information have made topical the problems of professional choice and judgment. Purpose. A systematic study of the special features of the work of accountants in Russia and the provision of relevant professional ethical principles. Justification of the conclusions obtained by combining the economic and psychological fields of knowledge. Methodology. The study is based on the following methods of scientific research: intellectual modeling, experimentation, deduction, analysis and synthesis of information. Results. The conclusions based on the results of the research using the data of social and psychological research on the peculiarities of various types of work activity indicate that the current Code of Ethics for Professional Accountants needs substantial improvement because it does not take into consideration the special professional features. Conclusions. In order to draw the attention of the professional community to the problems of professional ethical behavior of accountants and implement the relevant ethical principles on a wider basis, the Code of Ethics for Professional Accountants should be supplemented by such ethical principles as self-sufficiency, creativity, professional restraint, professional judgment steadfastness, professional conformism.